Determinants Factor Of Employee Performance: Evidence From UD Putra TS - Listiani, Devi; Apriliyani, Dini (IJBLE Scientific Publications Community Inc., 2024)
Good performance among team members is an important step to achieve a goal that has been implemented by an organization. Thus, an effort is needed to increase their productivity. The purpose of this study is to investigate the impact of adherence to work procedures and values embedded in the organizational structure on employee performance at UD Putra TS, Majalengka. This study focuses on UD Putra TS, Majalengka, and has a population sample of 150 employees. This study used a saturation sampling strategy, with data acquired by observation, interviews, and questionnaire distribution. The data analysis carried out by the researchers was using the linear regression method through SPSS software version 23. The analysis's findings demonstrate that organizational culture, which has also been shown to have a positive and significant impact on employee performance at UD Putra TS, Majalengka, and compliance with work procedures (work discipline) both positively and significantly affect employee performance at the school. Additionally, employee performance at UD Putra TS, Majalengka is positively and significantly impacted by both organizational culture and adherence to work processes (work discipline).